The acoustic aspects of voice in reflux-induced laryngitis and vocal fold polyp - Elaheh Akbari; Ali Ghorbani; Farzad Izadi; Farhad Torabinejad (Vesnu Publications, 2011)
Introduction: Bnign laryngeal lesions are relatively commonly occurring problems which are often noted after changes in voice. Since they are non-invasive and yield objective easy-to-collect data, acoustic laboratory methods are used along with perceptual assessments for evaluation of voice. Studying acoustic characteristics is useful in diagnosis and treatment of voice disorders.  With regard to the fact that polyps and reflux laryngitis result in similar auditory features of voice, this study aimed to find acoustic differences between these two conditions. Materials and Methods: in a  cross-sectional non-interventional retrospective study, a number of patients (both males and females) with vocal fold polyps and reflux laryngitis with the age range of  74 -20years were studied.  To determine voice characteristics of all participants, the vowel / æ / was analyzed using the software Praat.                                                                                                                                            Results  : The amounts of mean fundamental frequency(MF0), fundamental frequency range (RF0) and shimmer were higher in males with polyps than those with reflux laryngitis. RF0, shimmer and HNR values were significantly different in both groups. Comparison of MF0 and jitter variables of males with polyp and with reflux laryngitis with all voice characteristics of females in both groups showed no significant difference. Conclusion: Shimmer, RF0 and HNR values in men with polyp were different from these values in those patients with reflux laryngitis and these features are more affected in polyps than in reflux laryngitis. So these characteristics can be considered as the differential features (differentially diagnostic) in these two groups of patients. Keywords: Larynx pathologies, Vocal polyps, Reflux laryngitis, Voice disorder , Acoustic characteristics of voice